Model Pengukuran Stress Paramedis Serta Implikasinya Terhadap Kinerja Dengan Struktur Equation Model (Studi Dibagian Icu Rs Santosa Bandung) - Hadiansyah, Hadiansyah; Sidqi, Abdul Gani; Sofia, Etty; Kosasih, Kosasih; Rulia, Rulia (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study aims to analyze the stress levels of paramedics in the ICU at Santosa Hospital Bandung and their impact on performance using Structural Equation Modeling (SEM). The research focuses on workload, skills, knowledge, and interpersonal disharmony, affecting paramedics' responsiveness, service quality, and technical capabilities. The findings reveal that high workload and insufficient skills significantly increase stress levels. Recommendations include providing medical skill training and optimizing workload management to support optimal performance. This study offers strategic insights for hospital management to create a better working environment